Prevalence and risk factors of tuberculosis in developing countries through health care workers. (November 2018) - Sharma, Divakar; Sharma, Juhi; Deo, Nirmala; Bisht, Deepa
Abstract: In the last two decades, tuberculosis (TB) have threatened the public across the globe and continuing new TB cases and their transmission pooled with the global emergence of drug-resistant strains present an enduring occupational risk for health care workers (HCWs). Since last decade, government and funding agencies has given a significant amount of funds to tackle the problem of TB infection among medical staff or HCW in hospitals of developing countries, but the effects of these efforts have not yet been reported. Working environments are the major risk factors for TB infections among the HCW in hospital settings. Twenty-two high burden countries endorsed to the preponderance of worldwide tuberculosis cases in 2015. Urgent preventive strategies and mediations are needed to ensure the safety and sustained availability of these exquisite healthcare resources. This timeline review will provide the theoretical basis of high TB burden among the HCW which can be used for further improvement in strategies for the prevention of TB infections in hospital settings and provide a reliable basis for improving the personal health of HCW or medical staff. Highlights: Tuberculosis prevalence is increasing among the medical staff or HCW in Indian hospital settings. Health care workers are at high risk of procuring tuberculosis through occupational exposure. Improvement in the strategies for the TB infections in hospitals settings of developing country is urgently needed.